Challenges and opportunities: for on-line marketing strategies - Norhilmi, Muhammad; Maryam, I.Y. Suleiman; Ibrahim Suleiman, Yahaya (SERSC, 2020)
Online marketing, this is also named internet marketing, makes use of digital, virtual spaces for the purpose of promoting and selling products and services. In addition, new synchronous, internet-based interaction technologies have led to the transformation of major economic industries like marketing. Be cost-effective, fast and enjoying an on unparalleled global scope, internet marketing has brought about various businesses tremendous gains. However, this impactful, new approach also includes its special difficulties, e.g. lack of face to face contact, privacy, and security, etc which should be considered as part for. The present study, concentrates upon the impacts of internet-fostered digital spaces on marketing practice and also showing the review of different marketing strategies which, a business can apply toward the achievement of its goal. The paper starts with describing online-marketing and evaluating historical background to use online-marketing; various methods of online marketing, online marketing-strategy different argument by various authors, which some light shall be shed on. The marketing possibilities prevent from the introduction of this new, virtual space are the next focal point. The research continues with issues, such as security and privacy issues, lack of trust etc., that arose from virtual space deployment in the marketing area. Contemplating the answers to the problems that lie ahead, we propose the conclusions.